Enhancing Spinach (Amaranthus tricolor L.) Growth Using Maggot Fermentation-Derived Liquid Organic Fertilizer and AB Mix in Drip Fertigation Systems - Sugiarto, Yusron; Nugrayani, Thalia Reninang; Hakim, Luchman; Djoyowasito, Gunomo; Zhang, Juan (Universitas Brawijaya, 2024)
Spinach (Amaranthus tricolor L.) is a highly nutritious leafy vegetable widely cultivated for its rich content of vitamins and minerals. To enhance spinach production sustainably, this study investigates the use of liquid organic fertilizer derived from maggot fermentation combined with AB mix nutrients, applied through a drip fertigation system. The study was conducted using three different concentrations: 2.5 ml/L, 5 ml/L, and 7.5 ml/L, with the goal of identifying optimal conditions for maximizing spinach growth. The research utilized a two-factorial, Completely Randomized Design (CRD) with five replications to evaluate the effects of these nutrient combinations on key growth parameters, including plant height, leaf number, leaf area and weight of plants. Results indicated that a concentration of 7.5 ml/L provided the most favorable growth outcomes, with a 46.5 cm increase in plant height and a biomass accumulation of 61.8 grams, representing significant improvements over control treatments. The macro-nutrient content of the maggot-derived POC met national agricultural standards, except for pH, which improved to 7.10 when combined with AB mix. These findings suggest that integrating maggot POC with AB mix offers a cost-effective and environmentally friendly alternative to conventional fertilizers, promoting sustainable agricultural practices. This study contributes to developing efficient cultivation methods for spinach, addressing increasing market demands, and reducing reliance on chemical fertilizers.